The 2024 hajj special committee: Analyzing the complexities of social and media realities through the lens of social construction theory - Khakim, Abdul (Islamic perspective on Communication and Psychology, 2025)
Background: The issue of organizing the 2024 Indonesian Hajj seems more complex because it presents many diverse social or media realities. This paper aims to critically analyze the diversity of these realities based on the Social Construction theory conceptualized by Peter L Berger and Thomas Luckmann. Methods: The research of this paper uses a qualitative approach from data collected in mainstream media and social media and is supported by data from research, discussions and interviews. Findings: From a critical analysis, it shows that the social reality in the issue of the Special Hajj Committee and the 2024 Hajj service is not singular. Moreover, the media reality is also very complex and counterproductive to each other. Conclusion: The findings reveal that the discourse on the Special Hajj Committee and the 2024 Hajj service is shaped by multiple, sometimes conflicting, social and media realities. These complexities highlight the non-singular nature of social constructions in Hajj management, where differing narratives influence public perception and policy debates. Novelty/Originality of This Study: The novelty of this study lies in its application of Peter L. Berger and Thomas Luckmann's Social Construction theory to critically analyze the diverse and often conflicting social and media realities surrounding the 2024 Indonesian Hajj, providing a nuanced understanding of how narratives shape public perception and policy discourse.